Pengembangan Virtual Lab Berbasis Alternative Solution Worksheet Materi Rangkaian Listrik Sederhana Sekolah Dasar - M Iqbal Arrosyad; Fandi Nugroho (Universitas Muhammadiyah Bangka Belitung, 2025)
Practical difficulties often hinder students' understanding of simple electrical circuits. Confirmative practicums limit creativity as they do not provide opportunities for students to explore experiments independently. Furthermore, traditional practicums fail to accommodate diverse conceptual levels, including high and low electrical flow comprehension. To address these challenges, this study aimed to develop a virtual lab supplemented with an alternative solution worksheet for teaching simple electrical circuits to elementary school students. The research employed the Alessi & Trollip development model, encompassing three stages: planning, designing, and developing. Each stage involved continuous evaluations to ensure the quality of the developed product. Data collection methods included observations, interviews, and questionnaires, with validation performed by material and media experts. Data analysis utilized qualitative descriptive techniques to assess the product's effectiveness. The results indicated that the material validation test achieved an average score classified as